Construct validity of the physical activity neighborhood environment scale-Oman - De Siqueira, Gustavo; Mabry, Ruth; Al Siyabi, Huda; Adeel, Ahmad; Malaj, Sadmira; Oyeyemi, Adewale (Frontiers in Public Health, 2023)
Aims This study aims to examine the construct validity of Physical Activity Neighborhoods Environment Scales, Oman (PANES-O), and compare the subjective perceptions with objective measures in Muscat, the capital area of Oman. Methods Walkability index scores using GIS maps were calculated for 35 study areas in Muscat based on which five low and 5 high walkable study areas were randomly selected. A community survey was then conducted in November 2020 in each study area using the 16-item PANES-O instrument to measure the participants' perception of neighborhood density, land use mix, infrastructure, safety, aesthetics, and street connectivity. Due to pandemic restrictions, a social media-based purposive sampling strategy was utilized to reach community-based networks and complete digital data collection. Results Significant differences between the low and high walkablehigh-walkable neighborhoods were observed for 2 of 3 macroenvironment subscales, density and land use. Respondents in high walkable neighborhoods perceived their areas as having more twin villas (P = 0.001) and apartment buildings (P < 0.001), greater access to destinations (like more shops, and places to go within walking distance; P < 0.001), easy access to public transport (P < 0.001), and more places to be active (P < 0.001); than their counterparts in low walkable neighborhoods. In terms of microenvironmental attributes, respondents in high walkablehigh-walkable neighborhoods perceived their areas to have better infrastructure, better aesthetic qualities, and better social environment than their counterparts in low walkablelow-walkable neighborhoods. Significant differences in perceptions across 12 of the 16-item PANES tool confirmed that 6 of the 7 subscales were significantly sensitive to built environment attributes between the low and high walkable study areas. Respondents in high walkable neighborhoods perceived their areas as having greater access to destinations (like more shops, places to go within walking distance; P ≤ 0.001), easy access to public transport (P ≤ 0.001), more places to be active (P ≤ 0.001), better infrastructure (like more sidewalks, facilities to bicycle; P ≤ 0.001), and better aesthetic qualities (P ≤ 0.001). PANES-O also was able to rate high walkable neighborhoods to be higher in residential density and land-use mix compared to the low walkable neighborhoods demonstrating its sensitivity to the GIS maps' objective measures. Conclusions and recommendations These results provide preliminary strong support for the construct validity of PANES-O, suggestingconfirming that it is a promising tool for assessing macroenvironmental perceptions related to physical activity in Oman. Further research using objective measures of microenvironments and device-based physical activity scores is needed to confirm the criterion validity of the 10 micro-environmental attributes of PANES-O using objective measures for the microenvironment. PANES-O could be used to generate and develop the needed evidence on the most appropriate approaches to improving the built environment to promote physical activity and urban planning in Omanthe country.